THE EFFECT OF WATER AND NILA FISH (OREOCHROMIS NILOTICUS) SAMPLES MATRIX IN DETERMINATION OF PHENOL, m-NITROPHENOL AND m-AMINOPHENOL COMPOUNDS BY HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC) - Aloisia Uron Leba, Maria
Phenol and its derivates are pollutant which have high toxicity to aquatic organism and may cause bioaccumulation. Content of phenolic compounds in various environmental samples has been determined, but there are some complex sample matrix therefore requires preparation. Many of methods have been used to eliminate and reduce the matrix, but it can not applied to different samples. The aim of this research are to determine the effect of water and fish sample matrix for determination of phenol, m-nitrophenol (m-NP) and m-aminophenol (m-AMP) and to validate the method used. This research was conducted by high performance liquid chromatography – reverse phase (HPLC-RP) and solid phase extraction (SPE) method. Research showed matrix of fish samples interfere m- AMP determination especially at low concentration, while the water sample matrix does not interfere the determination of those three compounds. Linearity of this method was 0,999 for phenol, 0,994 for m-NP and 0,971 for m-AMP. Relative standard deviation (RSD) of reproducibility based on peak area was 2,100% – 8,039%; 4,449% – 13,690% and 11,167% – 29,850% respectively for phenol, m-NP and m-AMP. RSD of reproducibility based on retention time for the phenol and m-NP were less than 4%, m-AMP was less than 10%. RSD of repeatability based on peak area and retention time for the three compounds respectively less then 8% and 3%. Recovery of SPE method for phenol, m-NP and m-AMP are 96,77; 91,570 and 76,270%. Limit of detection and limit of quantization respectively for phenol was 0,387 ppm and 1,290 ppm, for m-NP was 0,189 ppm and 0,630 ppm, for m-AMP was 0,906 ppm and 3,019 ppm.